A SECURED DATA DEDUPLICATION IN CLOUD STORAGE WITH CHUNKING AND HASHING - et al., Saravanan K (International Journal of Advanced Science and Technology, 2019)
Storage services are offered by cloud computing in which data are stored, managed, archived in remote virtual machines and made for user availability through internet. Data duplication is a process of creating exact copy of same data which occupies more space in the cloud storage. Thus data deduplication is used to reduce storage overhead by eliminating redundant copies of data within files and between files. Chunking is identifies as the initial process in data deduplication, which splits the file into chunks. Content defined chunking Algorithm splits file into variable length chunks based on the file content. Public key cryptography Algorithm is used for encryption of file and to preserve privacy. Novel chunking algorithm is used for finding cut point and splits files into chunks which are then passed into Counting Bloom Filter that returns hash type according to which either one of non-cryptographic hash function is used. Results of various graphs shows that proposed method is best in all cases with minimum time taken (Hashing time, chunking time and deduplication time) and gives high throughput and deduplication ratio.